Radiation-induced lung injuries after modern radiotherapy methods - Heletsi, Selasi Abla (Univerzita Pardubice, 2022)
This bachelor's thesis introduces the modern techniques used in radiation therapy of thoracic malignancies. The theoretical part is devoted to describing the susceptibility of the lungs to radiation injury during radiotherapy with the use of modern radiotherapy techniques, and describing these injuries. The practical part assesses the effects of conformal radiotherapy techniques compared to conventional radiotherapy techniques in thoracic cancer patients, their effects on healthy tissues, and the prevalence of lung injuries.
Radiačně indukované poškození plic po využití moderních metod radioterapie
Keywords: plíce; poškození plic; radioterapie; radiosensitivita; radiační fibróza; radiační pneumonitida; lungs; lung injury; radiotherapy; radiosensitivity; radiation fibrosis; radiation pneumonitis